Analisis Kesalahan Peserta Didik Dalam Menyelesaikan Soal Matematika Kelas VII SMP Negeri 18 Padang - EGI SILVIA (Departemen Matematika, 2019)
Students make mistakes in solving math problems because the mastery of the students ' material is not good. To find out the learners ' mistakes need to be analyzed. Teachers have not conducted student error analysis. The research aims to describe the types of student mistakes in solving math problems. In this study are limited to quadrilateral and triangular material. The approach taken in this study is qualitative research with a type of descriptive research. Data collection techniques with observation, test and poll methods. Data analysis techniques are done by reducing data, presenting data, and verifying data. The subject of this study is a student in class VII-5 SMP Negeri 18 Padang. Students ' mistakes are conceptual, procedural and technical mistakes. Based on these results, it is obtained that many students make mistakes such as conceptual, procedural, and technical, as well as learners do not understand the formula, do not understand the working step, and not skilled in calculations. Of the 3 types of mistakes the most accomplished mistake by learners is conceptual and procedural mistakes and few learners experience technical errors.Keywords: Error analysis, conceptual error, procedural errors, technical errors